2001
DOI: 10.1007/s001980170034
|View full text |Cite
|
Sign up to set email alerts
|

The Tromsø Study: A Population-Based Study on the Variation in Bone Formation Markers with Age, Gender, Anthropometry and Season in both Men and Women

Abstract: Background information on how biological factors influence the level of bone turnover markers is crucial in order to make proper use of these measurements. In the present study, which is part of the fourth survey of a general population in Tromsø, Norway, we evaluated the variation in the bone formation markers bone alkaline phosphatase (S-BAP) and osteocalcin (S-OC) in 528 men and 605 women, age 25-74 years. In the Tromsø Study in 1994/5, the whole population above 25 years was initially invited and 7948 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
4
19
1
3
Order By: Relevance
“…The rate of bone loss is determined by a number of factors, one of which appears to be the rate of bone remodelling. Earlier observations demonstrated that bone formation and bone resorption increase shortly after natural menopause; a phase that in most women is also associated with significantly accelerated bone loss (4,5,(8)(9)(10)(11)(12)(13)(14). Similar observations have been made in ovariectomized, premenopausal women and in castrated men (56,57), indicating that the withdrawal of endogenous sex steroid induces both high bone turnover and rapid bone loss.…”
Section: Bone Turnover and Bone Losssupporting
confidence: 52%
See 1 more Smart Citation
“…The rate of bone loss is determined by a number of factors, one of which appears to be the rate of bone remodelling. Earlier observations demonstrated that bone formation and bone resorption increase shortly after natural menopause; a phase that in most women is also associated with significantly accelerated bone loss (4,5,(8)(9)(10)(11)(12)(13)(14). Similar observations have been made in ovariectomized, premenopausal women and in castrated men (56,57), indicating that the withdrawal of endogenous sex steroid induces both high bone turnover and rapid bone loss.…”
Section: Bone Turnover and Bone Losssupporting
confidence: 52%
“…After that, a slight increase is usually seen in both formation and resorption markers (4-7). In contrast, menopause is associated with a substantial acceleration in bone turnover, mirrored by a 50-100% increase in both markers of bone formation and resorption (4,5,(8)(9)(10)(11)(12)(13)(14). In early postmenopausal women, this increase in bone turnover can be attenuated by oral calcium supplementation (15)(16)(17)(18)(19).…”
Section: Menopause and Ageingmentioning
confidence: 99%
“…(20)(21)(22) There may be other factors influencing serum osteocalcin concentrations such as the use of oral contraceptives (23,24) hormone replacement therapy (25) and BMI. (26) Furthermore, serum osteocalcin concentrations were reported to be increased for short term by calcium intake.…”
Section: Discussionmentioning
confidence: 99%
“…Terdapat percanggahan pendapat dalam pola perubahan PPT berdasarkan umur dalam kalangan lelaki. Pola perubahan berbentuk penurunan linear (Wishart et al 1995), dua fasa ataupun quadratik (Midtby et al 2001;Szulc et al 2001) telah dilaporkan. Kewujudan perbezaan pada aras PPT di antara kumpulan etnik masih dipertikaikan kerana kehadiran dan ketidakhadiran perbezaan tersebut pernah dilaporkan (Henry & Eastell 2000;Leder et al 2007).…”
Section: Pengenalanunclassified
“…Walau bagaimanapun, aras PPT paling rendah biasanya dijumpai pada umur yang lebih lewat menurut kajian lain berbanding dengan kajian ini. Midtby et al (2001) mendapati dalam kalangan lelaki berumur 25-74 tahun yang menyertai Kajian Tromso, aras OC mengikut umur adalah berbentuk quadratik dengan titik nadir pada 56 tahun (Midtby et al 2001). Kajian Szulc et al (2001) juga mendapati taburan quadratik pada aras OC dalam kalangan lelaki 18-85 tahun dengan titik nadir pada 56-60 tahun (Szulc et al 2001).…”
Section: Pengukuran Antropometri Badanunclassified